Total hip arthroplasty; indications, historical overview, surgical techniques, complications, and outcomes - Kania, Agata; Gonet, Malwina; Miszczyk, Karolina; Serwik-Trandasir, Aleksandra; Włodarczyk-Cybulska, Karolina; Maj, Patrycja; Sergiel, Natalia; Mozer, Piotr; Maternia, Jakub; Lazar, Michał (Journal of Education, Health and Sport, 2023)
Introduction and purpose Total hip arthroplasty (THA) has revolutionized the treatment of various hip pathologies. This method of treatment leads to significant pain relief, improved function, and enhanced quality of life for patients worldwide. The following article provides an extensive overview of THA; covering indications, historical overview, surgical techniques, complications, as well as outcomes. Material and method The authors had analyzed both PubMed, as well as Google Scholar databases using the following key words: ‘THA’; ‘total hip replacement’; ‘total hip arthroplasty’; ‘hip’; ‘direct anterior approach’; ‘direct lateral approach’; ‘posterior approach’; ‘THA outcomes’. Conclusion THA is considered to be one of the most clinically successful and cost-effective medical procedures, which were developed during the last century. What is worth mentioning, the world’s highest-impact academic journal, The Lancet, called THA ‘the operation of the century’ in the year 2007. The historical perspective of total hip arthroplasty reveals the remarkable journey of medical pioneers who paved the way for modern techniques and materials. From the early days of simple hemiarthroplasty to the development of innovative prosthetic components and minimally invasive approaches, the field has undergone substantial progress, resulting in improved patient outcomes and longevity of the implants. Despite these advancements, the review highlights several challenges and complications associated with total hip arthroplasty. Through continued investment in research, and collaboration among orthopedic surgeons, engineers, and researchers, addressing these challenges can lead to further improvements and enhanced patient experiences.